2009
DOI: 10.1029/2008jb005644
|View full text |Cite
|
Sign up to set email alerts
|

Determination of rapid Deccan eruptions across the Cretaceous‐Tertiary boundary using paleomagnetic secular variation: 2. Constraints from analysis of eight new sections and synthesis for a 3500‐m‐thick composite section

Abstract: [1] The present paper completes a restudy of the main lava pile in the Deccan flood basalt province (trap) of India. Chenet et al. (2008) reported results from the upper third, and this paper reports the lower two thirds of the 3500-m-thick composite section. The methods employed are the same, i.e., combined use of petrology, volcanology, chemostratigraphy, morphology, K-Ar absolute dating, study of sedimentary alteration horizons, and as the main correlation tool, analysis of detailed paleomagnetic remanence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
194
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(197 citation statements)
references
References 79 publications
2
194
1
Order By: Relevance
“…Although we cannot positively identify a causal mechanism for the speciation downturn in dinosaurs, there are many possible global phenomena that occurred during the Cretaceous Period [e.g., the continued breakup of the supercontinents Laurasia and Gondwana (limiting free movement and eventual para-or peripatric speciation), intense prolonged volcanism (36), climate change (37-39), fluctuations in sea levels (34,40), and ecological interaction with rapidly expanding clades (41)]. To accurately identify causal mechanisms of Mesozoic dinosaurian demise, we recommend that future studies focus on a longer time period than just the last 10-20 My of the Cretaceous (4,13,42,43).…”
Section: Significancementioning
confidence: 99%
“…Although we cannot positively identify a causal mechanism for the speciation downturn in dinosaurs, there are many possible global phenomena that occurred during the Cretaceous Period [e.g., the continued breakup of the supercontinents Laurasia and Gondwana (limiting free movement and eventual para-or peripatric speciation), intense prolonged volcanism (36), climate change (37-39), fluctuations in sea levels (34,40), and ecological interaction with rapidly expanding clades (41)]. To accurately identify causal mechanisms of Mesozoic dinosaurian demise, we recommend that future studies focus on a longer time period than just the last 10-20 My of the Cretaceous (4,13,42,43).…”
Section: Significancementioning
confidence: 99%
“…Research between the late 1980s to the turn of the millennium (summarized by Courtillot and Renne, 2003) showed that during large igneous province volcanism, the climax or peak in terms of erupted lava volume was often much less than 1 m.y. in duration Courtillot, 1999;Chenet et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For another example, the Deccan Traps fl ood basalts were previously believed to have erupted over a period of ~5 m.y., based on the large range of early age determinations (see Vandamme et al, 1991). Redating of the basalts using refi ned Ar/Ar techniques, combined with paleomagnetic studies of the lavas, however, indicates that much of the Deccan lavas were erupted over a period of only ~500,000-800,000 yr (Chenet et al, 2009). The entire duration of Deccan volcanism may have been ~3 m.y., although this still remains to be thoroughly documented.…”
mentioning
confidence: 99%
“…Because the pervasive alteration makes it very difficult to impossible to observe any petrologic break within Unit V (see "Petrography"), we concluded that these individual lava units are themselves stacked (grouped) together into one "lava package" representing a short eruptive period of continuous build-up of lava units. As no interbedded sediment was recovered, the succession of inflation units in Hole U1346A likely represents a continuous "single eruptive event" (Chenet et al, 2009) during which successive pods or pillows were produced and stacked in a single package one upon another (Table T5). …”
Section: Expedition 324 Scientists Site U1346mentioning
confidence: 99%